Cenários do turismo rural de base comunitária : atuação do projeto Dom Távora na microrregião de Brejo Grande-SE - Santos, Elis Gardênia dos (2021)
This research aimed to verify the performance of the Dom Távora Project (PDT) in the Brejo Grande microregion, in the state of Sergipe, specifically analyzing the possibilities offered regarding Community Based Rural Tourism (TRBC). The corpus of analysis consisted of quantiqualitative data from official the PDT documents and narratives of project beneficiaries built from an interview with a structured question. The data were analyzed using a combination of methods, including statistical representations of the quantitative data resulting from analyzes of the official documents of the PDT and textual analyzes of the qualitative data resulting from the interviews. Direct observation was also used as a complementary instrument for data analysis. The study was contextualized from socio-environmental and economic references in the region, dialoguing with theoretical references from the environmental field and tourism, especially studies that approach perspectives of TRBC with a focus on environmental sustainability. Among the results of this dissertation, the following stand out: (a) a better understanding of possibilities and limitations for TRBC from the practice of a project that was already implemented; (b) possibilities to overcome the specific difficulties for implementing TRBC in the Brejo Grande micro-region, recognizing the region's potential for TRBC and the socio-environmental and economic benefits that this activity could offer to local communities; (c) contributions to the larger project to establish a Tourism Route in the Lower São Francisco region, recognizing the socioenvironmental-economic benefits that this project could offer to local communities.